Services outsourcing and innovation: an empirical investigation - Holger Görg; Aoife Hanley (Institute for the Study of Labor (IZA), 2009)
We provide a comprehensive empirical analysis of the links between international services outsourcing, domestic outsourcing, profits and innovation using plant level data. We find a positive effect of international outsourcing of services on innovative activity at the plant level. Such a positive effect can also be observed for domestic outsourcing of services, but the magnitude is smaller. This makes intuitive sense, as international outsourcing allows more scope for exploiting international factor price differentials, therefore giving the establishment higher profits and more scope to restructure production activities towards innovation. We also find that international services outsourcing has a positive effect on profitability, as predicted by theory, while this is not true for domestic sourcing. The results are robust to various specifications and an instrumental variables analysis.
Keywords: F19; O31; 330; Services outsourcing; offshoring; innovation; R&D; Unternehmensdienstleistung; Outsourcing; Offshoring; Rentabilität; Innovation; Industrielle Forschung; Irland